Pengaruh Perkembangan Kehidupan Masyarakat terhadap Pengaturan Hukum tentang Aborsi di Indonesia - Paulinus Soge (Jurnal Hukum IUS QUIA IUSTUM, 2000)
The purpose of this article is neither to explore the evolution of US Supreme Court doctrine concerning abortion, nor to discuss about the controversy on abortion issue occurred at The International Conference on Population and Development (ICPD) in Cairo in September 1994. The discussion is directed to the area of legal policy to anticipate a legal change on abortion in Indonesian Penal Law from "illegal" to "legal" under certain requirements (safe abortion) to prevent women doing unsafe abortion resulting in increasing number of maternal death. To design such an abortion law in Indonesia it is recommended to leam the development of abortion law in various countries especially after the ICPD